Hypoxia‐mediated alteration in cholesterol oxidation and raft dynamics regulates BDNF signalling and neurodegeneration in hippocampus. Issue 2 (7th December 2018) - Sharma, Deepti; Barhwal, Kalpana Kumari; Biswal, Surya Narayan; Srivastava, Anup Kumar; Bhardwaj, Pushpendar; Kumar, Ashish; Chaurasia, Om Prakash; Hota, Sunil Kumar
Abstract: Brain‐derived neurotrophic factor (BDNF) which is primarily associated with neuronal survivability, differentiation and synaptic plasticity has been reported to mediate neurodegeneration in hypoxia through its p75 Neurotrophin receptors (p75NTR). The molecular events promoting BDNF‐mediated pro‐death signalling in hypoxia, however, still remain an enigma. This study attempts towards deciphering the signalling cascades involved in alteration of BDNF isoforms and its cognate receptor subtypes leading to neurodegeneration in hypoxia. Adult Sprague–Dawley rats were exposed to global hypobaric hypoxia simulating an altitude of 7620 m at standard temperature and humidity. Chronic hypoxic exposure for 7 days resulted in higher expression of pro‐BDNF and alteration in N‐linked glycosylation in hippocampus along with increased expression of endoplasmic reticulum stress markers viz., glucose‐regulated protein (Grp78), calnexin and changes in the endoplasmic reticulum morphology. Our findings reveal enriched expression of p75NTR in lipid rafts and higher expression of tyrosine receptor kinase β (Trkβ) in non‐raft regions following hypoxic exposure. Further investigations on membrane properties revealed decline in membrane fluidity along with increased cholesterol oxidation resulting in reduced translocation of Trkβ from non‐raft to raft regions. Supplementation of vitamin E during hypoxic exposure on the other hand reduced cholesterol oxidation and increased translocation of Trkβ from non‐raft to raft regions and promoted neuronal survival. Hence, our findings suggest a novel mechanism of cholesterol oxidation‐induced alteration in raft dynamics which is promotes p75 receptor‐mediated death signalling in hippocampal neurons during chronic hypoxia. Abstract : BDNF mediated neurodegeneration in hypoxia through p75 neurotrophin receptor. however, underlying mechanisms are unknown. The present study attempts towards deciphering the signalling cascades involved in alteration of BDNF isoforms and its cognate receptor subtypes leading to neurodegeneration in hypoxia. Our finding revealed Hypoxia induced endoplasmic reticulum stress alters glycosylation of pre‐proBDNF leading to increased expression of pro‐BDNF. Hypoxia also results in increased localization of p75/p75 dimers in the raft fraction resulting in death receptor mediated apoptosis of hippocampal CA1 neurons. Future studies in this direction may provide a breakthrough in developing suitable prophylactic and therapeutic strategies for ameliorating hypoxic neurodegeneration.